(untitled) (Innovaciones Educativas, 2022)
This work describes and analyzes the experience acquired in remote emergency teaching due to the pandemic caused by the virus responsible for COVID-19 during the development of the Physics class at Universidad Nacional de Tucumán (Argentina). The Chair had to adapt its teaching strategies from face-to-face to non-face-to-face modality, thus, allowing students to continue their studies. An online didactic proposal was developed and applied with a constructivist approach that included the design of a virtual classroom and using various digital resources. The contents were organized into eight thematic units. The laboratory practices were designed to be carried out virtually. The final evaluation was conducted synchronously and remotely, while the communication was organized synchronously and asynchronously. Some indicators (attendance, access to the classroom, video visualization time, grades) on the teaching and learning processes were analyzed regarding the designed didactic strategies and evaluation. The evaluations expressed by the student body on different aspects through a survey were also analyzed, which were positive. A high percentage of attendance and access to the virtual classroom were observed. Likewise, viewing the videos was complete but fractional, and the average ratings were adequate. Finally, specific proposals were made to improve and optimize the teaching practice and students’ academic performance.